El Salvador : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
El Salvador has made major strides on several fronts since the peace accords of 1992. The near-term outlook has strengthened, although challenges remain. The authorities are intended to limit tax exemptions and subsidies, and raise priority of banking reforms this year. Discussions focused on policies to enhance growth and social progress within the framework of formal dollarization. IMF staff supported plans to consolidate financial stability through steps to strengthen the prudential and supervisory framework, deepen intermediation, and improve the safety net.